Knowledge as a predictive factor for self-care adherence and glycemic control of people with diabetes - Silva, Walesson Inácio dos Santos (2020)
This study sought to analyze the knowledge of diabetic people about their disease and its relation with self-care adherence and glycemic control. This is a descriptive study with a quantitative approach. Interviews were conducted with the aid of instruments for data collection. Fifty-two type 2 diabetic patients participated in the research. Data collection took place from January to April 2018 in a non-governmental organization in the metropolitan region of Belém. There was a prevalence of female patients (51.92%), aged between 60 and 69 years (40.38%) with incomplete primary education (34.60%), non-smokers (100%) and non-alcoholics (94.4%). Data on clinical characterization, complications of diabetes, knowledge about the disease and self-care adherence, and glycemic control showed that patients' knowledge was predictively related to adherence to drug treatment, but was not determinant for adherence to non-drug treatment. The data collected support the reflection of health professionals and the scientific community on the importance of knowledge and education in the treatment of diabetes, which proved to be predictive factors for drug treatment adherence in this study.